PELAKSANAAN LAYANAN PENGADAAN BADANG DAN JASA SECARA ELEKTRONIK DI KABUPATEN LAMONGAN TAHUN 2023 - Jaelani, Yazid Suhada; Manar, Dzunuwanus Ghulam (Journal of Politic and Government Studies, 2024)
Implementation of the construction project tender system policy in Lamongan Regency. This research aims to analyze the implementation of the construction project tender system policy in Lamongan Regency, as well as evaluate its effectiveness and identify the obstacles faced in its implementation. The research method used is a qualitative method with a case study approach. Data was collected through in-depth interviews with various related parties, direct observation and documentation studies. The research results show that the implementation of the construction project tender system policy in Lamongan Regency is experiencing various challenges. Despite efforts to increase transparency and accountability, there are still problems related to compliance with procedures, corrupt practices, and lack of community involvement in the tender process. The effectiveness of implementing this policy is also closely related to the capacity of the relevant institutions in managing and supervising the implementation of tenders. This research provides recommendations for improving the implementation of construction project tender system policies in Lamongan Regency, including by increasing understanding and awareness of the importance of compliance with tender procedures, strengthening monitoring and control mechanisms, and increasing community participation in the tender process. It is hoped that the results of this research can provide input for local governments in improving the effectiveness of construction project tender policies in order to create better governance and clean government in Lamongan Regency